Cell-free biosensors for biomedical applications. (March 2020) - Voyvodic, Peter L.; Bonnet, Jerome
Abstract: Recent years have witnessed a rapid increase of the use of cell-free systems for biosensor engineering. Building on the past decade of synthetic biology research mostly performed in living cells, researchers have developed a variety of cell-free applications capable of detecting antibiotics, clinical biomarkers, or nucleic acid sequences from viral and bacterial pathogens. Cell-free systems allow for simple fine-tuning of circuit component stoichiometry and provide a nonliving alternative to whole-cell biosensors that could expedite their path through regulatory approval. In addition, many of these systems have been shown to exhibit increased stability upon lyophilization, potentially enabling point-of-care applications and use in low-resource settings where continuous cold-chain maintenance may be difficult. Here, we discuss the latest advances in cell-free biosensor research and highlight some key challenges to address for the field to bring its full potential.